"Non est misericordia vera nisi sit ordinata" : pastoral theology and the practice of English justice, c. 1100 – c. 1250 - Byrne, P; Philippa Byrne (2014)
This thesis examines the relationship, in theory and in practice, between the concepts of justice (iustitia) and mercy (misericordia) in English courts between c. 1100 and c. 1250. During this period English judges (in courts of both common and canon law) were faced with a serious dilemma. The emergence of systematic law had fundamentally altered the pastoral foundations of the act of judgement. On the one hand, judges were incorporated into a system of law in which justice was expected to be routine and regular. They were bound by procedure, and ‘justice’ was considered to lie in the return of due punishment for injury. On the other, this notion of strict justice coexisted with an alternative way of conceiving of judicial responsibilities, which emphasised that justice was incomplete unless it incorporated within it the principle of mercy. This tradition argued that, both for the benefit of the offender and the judge’s own soul, it was safer and more virtuous to mitigate the punishments prescribed by law. English judges were caught in a dilemma, and were, in effect, obliged to choose between two fundamentally opposed ideas of justice, and two starkly contrasting approaches to sentencing. This thesis argues that such a choice was a problem which concerned the schools of theology as much as it did the courts of law. It examines the attempts of theologians and lawyers to resolve the dilemma and provide practical counsel to judges. Scripture, classical philosophy and patristic texts were the key sources in a discussion of how judicial discretion should be exercised in choosing between punitive and merciful courses of action. Rather than conceiving of justice as a purely procedural exercise, English law, and English judges, appreciated that the act of giving judgement was a complex pastoral challenge.